Social Management as a Current Challenge for Management and Sustainability of Efficiency in Social Services - Lehoczká , Lýdia (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
The paper discusses the requirement to develop social management. It specifies the strategic and current intention for social services and emphasises its contribution to improving the quality of professional and managerial activities in this field and the sustainability of efficiency. The study states the major research findings identifying the essential elements of management in the statements of future professionals in social services through the acquisition of important competencies and the overall professionalization of their field.